Physical abuse after child protective services investigation and adolescent substance use. (December 2016) - Kobulsky, Julia M.; Holmes, Megan R.; Yoon, Susan; Perzynski, Adam T.
Abstract: The longitudinal pathways connecting physical abuse and substance use in child welfare-involved adolescents, a population with multiple risk factors for substance use problems, remain unclear. This study examined the relation between self-reported physical abuse among adolescents investigated by Child Protective Services (CPS) and later substance use, with a particular focus on exposure to physical abuse after CPS investigation as a potential contributing factor to this relation. Using data from the first National Survey of Child and Adolescent Well-being (NSCAW-I), a path analysis was conducted on a sample of 1079 adolescents aged 11–15 years who had recently been investigated by CPS. At baseline and 18-month follow-up, youths self-reported past-year physical abuse using the Parent-Child Conflicts Tactic Scale and past 30-day substance use frequency. At baseline, youths self-reported current internalizing and externalizing problems to the Youth Self Report. Path analysis revealed no significant relation between physical abuse at baseline and substance use at 18 months. Physical abuse at baseline was associated with higher levels of concurrent substance use and externalizing problems, which in turn predicted higher substance use at 18 months. Furthermore, physical abuse and externalizing problems at baseline predicted physical abuse at 18 months, which in turn was related to higher substance use at 18 months. The findings suggest that physical abuse after CPS investigation contributes to the development of adolescent substance use behaviors. Results indicate a need for innovative efforts to prevent physical abuse after CPS investigation, as well as assessment and treatment of substance use and externalizing problems at the point of investigation, to reduce future substance use in child welfare-involved adolescents. Highlights: This study examines pathways from physical abuse at maltreatment investigation to later adolescent substance use. Physical abuse after investigation contributed to later substance use. Externalizing symptoms at investigation were related to physical abuse after investigation. Later substance use was predicted by substance use and externalizing problems at investigation. Findings inform substance use and physical abuse prevention in child welfare adolescents.